Extensive multiregional urea elevations in a case-control study of vascular dementia point toward a novel shared mechanism of disease amongst the age-related dementias - Philbert, Sasha A.; Xu, Jingshu; Scholefield, Melissa; Patassini, Stefano; Church, Stephanie J.; Unwin, Richard D.; Roncaroli, Federico; Cooper, Garth J. S. (Frontiers in Molecular Neuroscience, 2023)
Vascular dementia (VaD) is one of the most common causes of dementia among the elderly. Despite this, the molecular basis of VaD remains poorly characterised when compared to other age-related dementias. Pervasive cerebral elevations of urea have recently been reported in several dementias; however, a similar analysis was not yet available for VaD. Here, we utilised ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) to measure urea levels from seven brain regions in post-mortem tissue from cases of VaD (n = 10) and controls (n = 8/9). Brainurea measurements from our previous investigations of several dementias were also used to generate comparisons with VaD. Elevated urea levels ranging from 2.2-to 2.4-fold-change in VaD cases were identified in six out of the seven regions analysed, which are similar in magnitude to those observed in uraemic encephalopathy. Fold-elevation of urea was highest in the basal ganglia and hippocampus (2.4-fold-change), consistent with the observation that these regions are severely affected in VaD. Taken together, these data not only describe a multiregional elevation of brain-urea levels in VaD but also implies the existence of a common urea-mediated disease mechanism that is now known to be present in at least four of the main age-related dementias.